A review and analysis of the infrageneric classifications published or used for Kalanchoe (Crassulaceae subfam. Kalanchooideae) from 2001 to the present, with reference to those published up to 2000 - Smith, Gideon F. (Phytotaxa, 2024)
The infrageneric classifications used or proposed for, and infrageneric names and combinations published in, Kalanchoe (Crassulaceae subfam. Kalanchooideae) from 2001 to the present are analysed. Only the ranks of subgenus, section, and series are involved; no new names or new combinations were published at other infrageneric ranks. The pertinent works of Gehrig et al. (early-2000s [2001]), Descoings (early- and mid-2000s [2003, 2006]), Smith & Figueiredo (late-2010s [2018]), Smith (early-2020s [2020–2023]), Shtein & Smith (early-2020s [2021]), and Smith et al. (early-2020s [2021]) were assessed to clarify the use of infrageneric ranks by these authors, and to determine which of these names have been validly published and are available for use in Kalanchoe. From this analysis of the infrageneric classifications of Kalanchoe during a period of just less than 25 years it is evident that: (1) one new subgenus name was validly published by Descoings in 2006 [K. subg. Calophygia]; (2) one new combination at the rank of subgenus was validly published by Smith & Figueiredo in 2018 [K. subg. Kitchingia]; (3) one new subgenus name was validly published by Smith in 2020 [K. subg. Fernandesiae]; (4) one new combination was validly published at the rank of section by Smith in 2020 [K. sect. Stellatipilosae]; (5) one new section name was validly published by Smith in 2021 [K. sect. Alatae]; (6) one new section name [K. sect. Invasores] and one new series name [K. ser. Vilana] were validly published by Shtein and Smith in 2021; (7) one new section name was validly published by Smith in 2022 [K. sect. Raveta]; (8) and (9) two new section names [K. sect. Rhombopilosae and K. sect. Streptanthae] were validly published by Smith in 2023; (10) one new combination [K. sect. Trichanthae] was validly published at the rank of section by Smith in 2023; (11) one, by then, existing section, K. sect. Alatae, was elevated to the rank of subgenus by Smith in 2023; and (12) one existing subgenus, K. subg. Calophygia, was reinstated and its circumscription substantially amended by Smith in 2023.